Analisis Normatif terhadap Hak Waris Perempuan dalam Perspektif Hukum Islam, Hukum Adat dan Hukum Perdata di Indonesia - Lollyta Julius; M. Sudirman; Benny Djaja (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2025)
This study aims to analyze the normative provisions regarding women's inheritance rights in three legal systems applicable in Indonesia, namely Islamic law, customary law, and civil law. These three systems have different legal bases, values, and mechanisms in regulating inheritance rights, especially regarding the position and rights of women as heirs. Islamic law determines women's inheritance shares based on the provisions of the Qur'an and Al-Hadith or As Sunnah with the principle of proportionality according to socio-economic responsibilities in the family. On the other hand, customary law is highly dependent on the local kinship system, whether patrilineal, matrilineal, or bilateral, which causes great variation in granting inheritance rights to women. Meanwhile, civil law originating from the Civil Code emphasizes equality between men and women in inheritance rights, without gender differentiation. This study uses a normative legal approach with a qualitative analysis method on primary and secondary legal materials. The results of the study show that although normatively civil law and several customary law systems provide space for equality, in social practice and cultural interpretation of women in obtaining inheritance rights, harmonization between legal systems is still needed, as well as increasing legal awareness in society for women. This study also emphasizes the importance of strengthening the role of the state and law enforcement officers in implementing inheritance rights for women.